Differences in Oleic Acid Levels in Matured Milk in the Nutritional Status of Breastfeeding Mothers with Normal and Chronic Energy Deficient - Sumule, Inka; Citrakesumasari, Citrakesumasari; Daud, Nurpudji Astuti; Salam, Abdul; Indriasari, Rahayu; Ibrahm, Erniwati (International Journal Papier Advance and Scientific Review, 2020)
This study aims to determine the oleic acid levels of mature breast milk and to analyze differences in oleic acid levels in mature breastfeeding mothers with chronic energy deficiency (KEK) nutritional status and normal nutritional status. This type of research is analytic observation with a cross sectional approach. The population in this study was mature breastfeeding mothers who were in the work area of ​​Sudiang and Sudiang Raya Public Health Centers. The sample in the study was breastfeeding mother's milk aged 2 weeks-6 months. The sampling technique used was purposive sampling method, a sample size of 38 consisting of 19 breastfeeding mothers and 19 breastfeeding mothers with normal nutritional status. Data were analyzed using the Manwithney test. The results of the study found that oleic acid levels in SEZ breastfeeding mothers were in the range of 0.7 - 1.7, with an average of 0.95 ± 0.198 and normal breastfeeding mothers, the oleic acid levels ranged from 0.6 to 1.4 with an average of 0 , 94 ± 0.195. The results of statistical tests found no significant difference p = 0.317 levels of oleic acid in breastfeeding mothers, the nutritional status of KEK compared to normal nutritional status. Oleic acid levels in breast milk for breastfeeding mothers with KEK were 94.7%, category less than the reference and in breastfeeding mothers the normal nutritional status was 100% lower than the reference level (1.5 gr / L).